Determination of satellite orbits and the global positioning system - Agrotis, Loukis George (1984)
An artificial satellite orbit determination (OD) computer program is the most essential tool in satellite geodesy. Such a program has been developed at Nottingham as part of this research and was tested with Satellite Laser Ranging (SLR) observations of the Laser Geodynamics Satellite (LAGEOS).